Raspberry-like supraparticles from nanoparticle building-blocks as code-objects for hidden signatures readable by terahertz rays - Stumm, Christopher; Szielasko, Klaus; Granath, Tim; Stauch, Claudia; Mandel, Karl (Materials Today Communications, 2018)
Supraparticles, i.e., raspberry-like microparticles which are composed of nanoparticles (iron oxide), reveal specific interaction properties with terahertz (THz) rays. Depending on the density of the clustering of the nanoparticles within the raspberry-like supraparticle, characteristic THz components are altered upon transmission. The clustering can be adjusted upon supraparticle assembly via modification of the nanoparticles’ surfaces. By employing very densely and very loosely clustered supraparticles, a graphical coding system can be developed which allows creating signatures that are hidden in the bulk of a material (an object) and are easily and unambiguously decodable with THz rays.
CRIS-Team Scopus Importer:2020-04-02
Keywords: anti-counterfeit; codes; markers; supraparticles; terahertz